Constraining shear strength of fault damage zone using geodetic data and numerical simulation - Li, Chenglong (2024)
Shear strength of damage zone, representing the stress threshold for rupture initiation, is a critical parameter in faulting mechanics. Despite its significance, the damage-zone's shear strength has not been estimated in natural earthquake ruptures. Here we employed coseismic deformation and strain, kinematic slip model, and finite element modeling to determine the elastic properties and peak shear stress of coseismic damage zones along the 2021 Mw 7.4 Maduo earthquake. Through the analysis of the lowest shear stress resulting in surface ruptures and the highest stress without surface rupture, we constrained the strength within a range of 7–17 MPa. Our result is consistent with strength (5–16 MPa) of sandstone samples from laboratory tests, demonstrating the validity of this estimation. Although factors such as fault maturity and confining pressure influence strength variation, the strength can directly reflect the stress threshold required for macroscopic surface rupture formation in fault damage zones dominated by sandstone.